Analysis of natural fiber polymer composites: Effects of alkaline treatment on sound absorption - Elammaran, Jayamani; Sinin, Hamdan; Muhammad Khusairy, Bin Bakri; Soon, Kok Heng; Md Rezaur, Rahman; Akshay, Kakar (SAGE Publications Ltd, 2015)
This study is focused on the development of sound absorbing materials based on natural fiber polymer composites. The natural fibers were modified through the alkaline treatment and the natural fiber polymer composites were fabricated using hot and cold compression hydraulic press machine. The sound absorption coefficients of the composites were measured using two-microphone transfer function impedance tube method. Characterizations of the natural fiber polymer composites were analyzed using scanning electron microscope and Fourier transform infrared spectroscopy. It was found that in all measured composites, the sound absorption coefficients increased as the frequency increased. Also, as the fiber loading increased, the sound absorption coefficients of the natural fiber polymer composites were increased. It was found that the alkaline treated fiber reinforced composites increased the sound absorption coefficients due to removal of impurities and change in the structure of composites. The alkaline treatment of fibers showed better adhesion interface between fiber and polymer as compared to untreated fibers. This can be seen clearly under morphological and spectral studies of the natural fiber polymer composites.